Sobre a variabilidade fotométrica em estrelas anãs brancas - Araújo, Suzierly Roque de Lira (2019)
Photometric variability can provide important information about white dwarfs, whether related to rotation or the presence of companions - planetary, substellar or stellar-remnant. The high photometric precision and the large amount of data provided by space missions, such as Kepler and K2, combined with the correct tools, make it possible to analyze the photometric variability of white dwarf stars. In order to detect the relative periodicities present in the light curve obtained by these space missions, several mathematical transformations have been applied, such as the Fourier transform, one of the most used in astrophysics, and the Wavelet, which has been applied in a wide range of areas. The Wavelet transform is a powerful tool, since it has functions located in both frequency and time, allowing the detection of the temporal evolution of various phenomena, which makes it ideal for analyzing non-stationary signals. In this context, we use these tools in order to study the photometric variability of 26 white dwarf stars observed by the Kepler mission. From the light curves of these stars, we analyze the Lomb-Scargle periodograms, determine the possible physical mechanisms responsible for the detected modulations and perform local and global wavelet spectra. The first one is interpreted as the signal energy distribution, while the second one is the temporal integration of the local map. Through this study, we detected periodicities between 0.09 and 20.04 days in 14 white dwarfs, which may be associated with rotation combined with other phenomena (magnetic starspots, accretion of gas from the interstellar medium, accretion of metals from a circumstellar debris disk, magnetic dichroism and optical fluorescence) that can occur in these stars, or, in at least one of the white dwarfs from our sample, the presence of close companions to this white dwarf. Finally, we discuss the physical meaning of the results by establishing a comparative study between the periodicities determined in this thesis and those found in literature for magnetic white dwarfs.